2023
DOI: 10.1093/ofid/ofad240
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of BA.1- and BA.4/BA.5-containing bivalent COVID-19 mRNA vaccines against symptomatic SARS-CoV-2 infection during the BA.5-dominant period in Japan

Abstract: In this multi-center prospective test-negative case-control study in Japan, the effectiveness of both BA.1-containing and BA.4/BA.5-containing bivalent COVID-19 mRNA vaccines against symptomatic infection during the BA.5-dominant period was high compared to no vaccination (65% and 76%) and moderate compared to monovalent vaccines administered over half a year before (46% combined).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…The emergence of breakthrough infections has led to the development of boosters with activity against the circulating SARS-CoV-2 variants [ 26 , 35 , 61 , 62 ]. Laboratory studies have shown that antibodies from persons boosted with original/Omicron vaccines had an increased neutralization capacity [ 60 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The emergence of breakthrough infections has led to the development of boosters with activity against the circulating SARS-CoV-2 variants [ 26 , 35 , 61 , 62 ]. Laboratory studies have shown that antibodies from persons boosted with original/Omicron vaccines had an increased neutralization capacity [ 60 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple test-negative case–control studies in the US, Japan, Korea, Israel and Nordic countries have shown decreased rates of hospitalization and death due to COVID-19 in those who received an original/Omicron vaccine relative to those who did not, with additional vaccine effectiveness ranging from 45 to 89%. The studies include different populations and different prior vaccine schedules [ 25 , 27 , 31 , 35 , 36 , 64 , 65 , 66 , 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, a few studies found prior infection could modify the efficacies of monovalent or bivalent boosters [37,50], but we were unable to stratify the VE estimates by prior infection status as most studies did not provide such information. Third, many studies included in this meta-analysis [21,22,29,32] did not specify the manufacturer or type of the bivalent booster and monovalent doses, introducing additional heterogeneity into and thus complicating the interpretation of our pooled results. This lack of granularity emphasizes the need for future studies to report VE estimates with greater specificity.…”
Section: Discussionmentioning
confidence: 99%
“…The initial recommendation included persons aged 12 years or more (Pfizer-BioNTech) and 18 years or more (Moderna) who had completed at least a primary series of an approved monovalent vaccine (with or without subsequent booster doses). Several studies have found that booster vaccination with adapted vaccines targeting BA.4/BA.5 and BA.1 are associated with levels of vaccine effectiveness at preventing infection and severe disease ranging from 46% to 88% [ 22 , 23 , 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%